Association of serum 25‐hydroxy vitamin D with obesity‐related indices in Chinese adults: A cross‐sectional study. Issue 4 (26th February 2021) - Ren, Zhongxia; Zhao, Ai; Wang, Yan; Meng, Liping; Man‐Yau Szeto, Ignatius; Yang, Chenlu; Wang, Meichen; Zhang, Jian; Wu, Wei; Wang, Peiyu; Zhang, Yumei
Abstract: Obesity has been a well‐known risk factor of low‐level serum vitamin D. Compared with the traditional obesity‐related indicator (body mass index, BMI), associations for two novel anthropometric indices, a body shape index (ABSI) and body roundness index (BRI) with vitamin D deficiency or insufficiency, still remain unclear. This study aimed to assess the associations of serum 25‐hydroxy vitamin D (25(OH)D) status with these three obesity‐related indices among Chinese adults. A total of 1666 individuals were included. Anthropometric measurements were performed to calculate the indices, and fasting blood was collected to determine serum 25(OH)D deficiency (<12 ng/ml) and insufficiency (12–20 ng/ml). Deficiency or insufficiency of 25(OH)D was found in 37.5% and 43.1% of the participants, respectively. After adjustment for potential confounders, a significantly increased prevalence of 25(OH)D deficiency was observed for higher ABSI (OR Q4 vs Q1 2.334, 95% CI 1.458–3.734; p trend  = 0.002) and BRI (OR Q4 vs Q1 2. 215, 95%CI 1.365–3.594; p trend  = 0.010), and for higher BMI in men. Regarding 25(OH)D insufficiency, a significant association was also found for ABSI (OR Q4 vs Q1 2.372, 95%CI 1.558–3.612; p trend  = 0.001). The area under the ROC of ABSI (0.731, 95%CI 0.687–0.774) for predicting a low level of 25(OH)D was significantly larger than that of BMI (0.695, 95%CI 0.649–0.741) in men, but not in women. A positive association between obesity and lower 25(OH)D serum concentration was found among Chinese adults. Besides BMI, novel obesity‐related indicator, ABSI and BRI were associated with lower serum 25(OH)D to some extent, and further studies are needed to clarify their potential to be used as screening tools in clinical practice. Abstract : A positive association between obesity and lower 25(OH)D serum concentration was found among Chinese adults. Besides BMI, novel obesity‐related indicator, ABSI and BRI were associated with lower serum 25(OH)D to some extent, and further studies are needed to clarify their potential to be used as screening tools in clinical practice.